A 12-week randomized double-blind parallel pilot trial of Sinetrol XPur on body weight, abdominal fat, waist circumference, and muscle metabolism in overweight men. (3rd June 2015) - Cases, Julien; Romain, Cindy; Dallas, Constantin; Gerbi, Alain; Rouanet, Jean Max
Abstract: Overweight and obesity are associated to increased risk of developing non-communicable diseases that might dramatically affect life expectancy according World Health Organization. Overweight, obesity, and decline in physical activity are correlated to a significant propensity to lose skeletal muscle mass as a result of prolonged inflammation and oxidative stress whereas cohort surveys and clinical investigations have demonstrated health benefits of Citrus -based polyphenols to reverse such regression. Overweight men were included in a double-blind, randomized, parallel pilot trial where they received daily for a 12-week period 900 mg of a Citrus -based polyphenol extract, Sinetrol® XPur. Body composition, anthropometric, and blood parameters were assessed before and at the end of the intervention period. After 12 weeks, while the silhouette slimmed down, metabolic parameters were significantly improved and skeletal muscle catabolism held back. These data suggest that over a 12-week period, the efficacy of the supplement improve both overweight process and correlated skeletal muscle mass metabolism.